Reappraisal and neotypification of Phyllachora feijoae - L.C. Costa; D.M. Macedo; R.W. Barreto (IMA Fungus)
Acca sellowiana (Myrtaceae), feijoa (in Brazil, goiaba da serra), is a native southern South America tree that produces edible fruits which, although only occasionally cultivated in South America, became a significant fruit crop in New Zealand. Recently, during surveys for fungal pathogens of feijoa in southern Brazil, several plants were found bearing tar-spot symptoms caused by a species of Phyllachora. A literature search enabled us to identify the fungus as Phyllachora feijoae, a little-known species originally described in the 19th century by H. Rehm and later transferred to the genus Catacauma. The name Catacauma feijoae, although now regarded as a later synonym of P. feijoae is still mistakenly in use (as, for instance, in the Brazilian list of fungi on plants). The type specimen was most probably deposited in the Botanisches Garten und Museum Berlin-Dahlem (B) and lost or destroyed during World War II, and could not be located. The recent recollection of abundant material of this fungus in the vicinity of Pelotas (Rio Grande do Sul, Brazil) allowed its re-examination and neotypification. Phyllachora feijoae is also illustrated here for the first time.